Olimpíadas de filosofia : por um ensino significativo - Machado, Marcos Antonio Dimas (2024)
This work aims to develop didactics for the event known as the Philosophy Olympiad for education in the state of Mato Grosso, based on empirical experiences in the classroom of state and private schools in the city of Sorriso-MT. To this end, we begin by defining the conception of Philosophy that we adopt, then we outline a brief history of the Philosophy Olympiads in the world, in South America and in Brazil, focusing on the one that served as inspiration for this work, which is the Rio de Janeiro Philosophy Olympiad, which uses the conception of Philosophy of Uruguayan professor Mauricio Langón, who develops the model of a non-competitive philosophical Olympiad. We demonstrate how we developed Langón's philosophy in the classroom and, finally, we propose a possible model for developing the phases of the Philosophy Olympiad in Mato Grosso.